Autonomous Survey in Northern Environments - MacKenzie, Ruairidh; Mallace, Duncan; Bazowsky, Dave; Day, M. (The International Hydrographic Review, 2021)
This note depicts the use of a next generation Uncrewed Surface Vessel for the collection of bathymetric data in inland Canadian waters, via a partnership between IIC Technologies and XOCEAN performing services for the Department of Fisheries and Oceans’ Canadian Hydrographic Service (CHS). It will discuss how the operation was successful, lessons learned and how operations in a quasi-subarctic environment from October to the end of November 2020 are a suitable test of the equipment and operations for near Arctic conditions. In addition, it will discuss recommendations on how autonomous technology could greatly improve the efficiency and effectiveness of hydrographic operations in Arctic waters, where there is a need for modern hydrographic data.